PEMANFAATAN BAN BEKAS UNTUK PERKUATAN STRUKTUR JALAN PADA PELEBARAN JALAN SOROWAKO – MALILI: SEBUAH KAJIAN TENTANG KESTABILAN GEOTEKNIK - Wiyatno Haryanto; Nendi Rohaendi; Ridwan Banda; Zufialdi Zakaria (PPSDM Geominerba, 2019)
PT Vale Indonesia Tbk is a subsidiary of Vale S.A. (Brazil) under Vale Base Metal group (Canada) located at Sorowako village, East Luwu regency, South Sulawesi province, in Indonesia, a foreign investment company in mining industry that running to explore, mine, process, and produce nickel in mate as an intermediate product. This paper is intended to introduce the “reusereduce-recycle” (3R) idea as an environmentally friendly concept by means of utilizing the scrap tires as alternative construction material for geotechnical engineering purposes. In terms of mining operational, PT Vale Indonesia Tbk consumes prefabricated tires that required for heavy equipment such as hauling trucks and wheel-loaders. Tire consumption for the mining operational is fluctuated ranging of 350–600 ea. per annum depending on some technical factors in example pavement condition, road geometry, braking frequency, payloads, et cetera. The large number of the current tire consumption is remaining a big problem in terms of availability of disposal (waste dump) to disposing the scrap tires. So far, the scrap tires are disposed merely into the waste dump as if a less valuable waste material. There is an idea to use scrap tires as construction materials. Geotechnical stability of the retaining structure made of the scrap tires are analyzed to obtain safety factor and reliable of the structure to stabilize the widening road in durable manner. The result of the research is that the utilization of scrap tires has fulfilled safety factor for long term about 1.46 without load seismic and 1.04 with load seismic.